The Role of Development Banks in the Economic Development Policy of the Republic of Korea - Neszmélyi, György Iván (Public Finance Quarterly, 2023)
The study offers an insight into the economic development policy of the Republic of Korea, in particular the activity and the role of development banks. Since the beginning of the 1960s, the particular and successful Korean way of economic development has been largely based on the Japanese model of the developmental state, which includes, as a peculiar factor, the strong directing role of the state (the government). Several decades ago the Korean government developed a complex and efficient incentive system that allowed the companies, in particular the Korean giant companies (chaebols) to become the locomotives of export-driven economic development, along with predefined industrial priorities. The Korean central bank (Bank of Korea), the Korea Development Bank and other development-oriented banks have played an important role in every phase of the economic development. By way of a proactive monetary and credit policy, the central bank of Korea facilitated to direct the country’s economic development into a solid track of growth in every critical period of the country’s history, from the times of the Korean war (1950–53) after the establishment of the Republic of Korea (1948), through the two oil shocks of the 1970s, until the economic and financial crises at the end of the 1990s and in the years 2008–2009. The Korean experiences, in particular the methods that allowed a swift recovery from the latest two crises may also be instructive from a Hungarian point of view as well.